3-D analytical model for bending stiffness of thick-walled composite hollow shaft. (April 2021) - Yang, Mo; Zhou, Yuebin; Zhou, Xian; Ye, Jianmin; Wang, Yikun; Qin, Tao; Zhang, Wen
In this paper, the Layer-wise theory was improve based on the alternate characteristics of layer angle of composite hollow shaft. The ±φi laminate was considered as the minimum mechanical analysis element, which can effectively simplify the stress coupling in mechanical analytical method. On this foundation, a 3-D analytical method of bending stiffness < EI > for thick-walled composite hollow shaft was derived. The CFRP hollow shaft specimens made of same dimensions but different laminate were used for bending test. Then, the bending stiffness calculated by theory of beams, 2-D analytical method, 3-D analytical model and experiment were compared. All the results show that the 3-D analytical model predicts the bending stiffness of thick-walled composite hollow shaft more precisely than the theory of beams and analytical method, and agree well with experimental results. And the 3-D analytical model can reflect the influence of stacking sequence on the bending stiffness of the composite hollow shaft.